Biometrics as security technology: Expansion amidst fallibility - Katja Lindskov Jacobsen (Danish Institute for International Studies (DIIS), 2012)
Biometric technology has been afforded a central role in the security architecture that Western governments have forged since the events of 9/11 2001. With biometrics the body becomes the anchor of identification. In a security architecture centred on identification of persons of interest and determination of their status as friend or foe, biometrics has come to be praised for its supposedly exceptional capacity to identify reliably. This report situates the use of biometrics as a security technology in relation to this promise of superior identification on the one hand and, on the other, to the various concerns that critics have raised. It argues that it is vital that decision makers acknowledge how biometrics is neither a flawless nor a politically neutral technology. Unless caution and concerns are taken seriously the risk is that biometrics will produce new forms of insecurity - rather than increased security.
Keywords: 300